Moderasi Beragama dalam Prespektif Filsafat Perenialisme - Muhammad Agus Nurrohman (Journal on Education, 2024)
Indonesia is a pluralistic country consisting various tribes, groups, religions, races and cultures whose been being able to live in harmony and have a very high negotiation space in every life however its situation and conditions. Beside that, Indonesian has a religious, polite and friendly local character. Meanwhile, religious moderation is an important issue in the world right now, including in Indonesia. The influence of globalization, religious pluralism, and technological advances have brought big changes to the dynamics of religious life. Perennialism as an educational philosophy was born on the 20th century, appearing as a reaction to progressivism education. Perennialism opposes progressivism opponion which emphasizes change and something new. According to Perennialism, the current world situation is full of chaos, uncertainty and irregularity, especially in moral, intellectual, spiritual and socio cultural life. It need an effort to save human culture from the brink of destruction. The concept of religious moderation can be understood from the perspective of perennial philosophy. Perennial philosophy emphasizes the existence of Holy entity or Oneness in every aspects in this life. According to the perennialisme thought, absolute truth is only one and it can’t be divided, but can be found in various truth. It can be found on history dialectical process. In this contexts of religious moderation, the idea of ​​perennial philosophy is used to understand religious plurality. Although understanding religion often cause one of factors of conflicts, understanding religious moderation teaches us how to pay attention in socio religious conditions outside of it’s own group and respecting different truths and beliefs